Microbiología de leches de origen bovino, procesadas para consumo humano - Páez Quinche, Miguel Ángel (2016)
The objective of this research was to analyze different brands of previously established milk, by targeting mothers who contribute to the essential samples and higher consumption, in order to know the quality of a food journal and consumer surveys. To carry out this work no experimental design was not used, since only is to evaluate and compare the results with established standards which allow presenting if these samples are within the established range of good quality or otherwise determine those do not meet the standards. In analyzes of pasteurized milk, it was determined that these meet the range specified in the INEN standards, still well below the established, so does the UHT milk, which show zero ranges or well below these wellbeing of excellent quality milk and good phytosanitary control. Regarding the analysis of antibiotics work samples determined that both pasteurized and ultrapasteurized were positive and in this area is determined that there is no adequate control for both processes.